Insights into size-segregated particulate chemistry and sources in urban environment over central Indo-Gangetic Plain - Singh N.; Banerjee T.; Murari V.; Deboudt K.; Khan M.F.; Singh R.S.; Latif M.T. (My University, 2025)
Size-segregated airborne fine (PM2.1) and coarse (PM>2.1) particulates were measured in an urban environment over central Indo-Gangetic plain in between 2015 and 2018 to get insights into its nature, chemistry and sources. Mean (±1σ) concentration of PM2.1 was 98 (±76) μgm−3 with a seasonal high during winter (DJF, 162 ± 71 μgm-3) compared to pre-monsoon specific high in PM>2.1 (MAMJ, 177 ± 84 μgm−3) with an annual mean of 170 (±69) μgm−3. PM2.1 was secondary in nature with abundant secondary inorganic aerosols (20% of particulate mass) and water-soluble organic carbon (19%) against metal enriched (25%) PM>2.1, having robust signature of resuspensions from Earth's crust and road dust. Ammonium-based neutralization of particulate acidity was essentially in PM2.1 with an indication of predominant H2SO4 neutralization in bisulfate form compared to Ca2+ and Mg2+-based neutralization in PM>2.1. Molecular distribution of n-alkanes homologues (C17–C35) showed Cmax at C23 (PM2.1) and C18 (PM>2.1) with weak dominance of odd-numbered n-alkanes. Carbon preference index of n-alkanes was close to unity (PM2.1: 1.4 ± 0.3; PM>2.1: 1.3 ± 0.4). Fatty acids (C12–C26) were characterized with predominance of even carbon with Cmax at n-hexadecanoic acid (C16:0). Low to high molecular weight fatty acid ratio ranged from 2.0 (PM>2.1) to 5.6 (PM2.1) with vital signature of anthropogenic emissions. Levoglucosan was abundant in PM2.1 (758 ± 481 ngm−3) with a high ratio (11.6) against galactosan, emphasizing robust contribution from burning of hardwood and agricultural residues. Receptor model resolves secondary aerosols and biomass burning emissions (45%) as the most influential sources of PM2.1 whereas, crustal (29%) and secondary aerosols (29%) were found responsible for PM>2.1; with significant variations among the seasons. © 2020 Elsevier Ltd